Assessment of medical students' leadership traits in a problem/case-based learning program. Issue 1 (1st January 2018) - Ginzburg, Samara B.; Schwartz, Jessica; Gerber, Rachel; Deutsch, Susan; Elkowitz, David E.; Ventura-Dipersia, Christina; Lim, Youn Seon; Lucito, Robert
ABSTRACT: Background : Healthcare delivery is shifting to team-based care and physicians are increasingly relied upon to lead and participate in healthcare teams. Educational programs to foster the development of leadership qualities in medical students are needed to prepare future physicians for these roles. Objective : Evaluate the development of leadership attributes in medical students during their first 2 years of medical school while participating in leadership training integrated into a problem/case-based learning program utilizing the Leadership Traits Questionnaire assessment tool. Design : Ninety-eight students enrolled at Zucker School of Medicine participated in Patient-Centered Explorations in Active Reasoning, Learning and Synthesis (PEARLS), a hybrid problem/case-based learning program, during the first and second years of medical school. The Leadership Traits Questionnaire, designed to measure 14 distinct leadership traits, was utilized. It was administered to students, peers in students' PEARLS groups and their faculty facilitators. Participants completed questionnaires at three-time points during the study. Likert scale data obtained from the questionnaire was analyzed using a two-level Hierarchal Linear Model. Results : Complete data sets were available for 84 students. Four traits, including self-assured, persistent, determined, and outgoing, significantly increased over time by measurements of both peer and facilitator-rated assessments. Six additional traits significantly increased over time by measurement of facilitator-rated assessment. By contrast, a majority of student self-rated assessments trended downward during the study. Conclusions : Medical students demonstrated development of several important leadership traits during the first 2 years of medical school. This was accomplished while participating in the PEARLS program and without the addition of curricular time. Future work will examine the impact of third year clerkships on leadership traits.